Legal Protection for Child Victims of Pedophilia Crimes from a Criminal Law Perspective - Budi Prayitno; M. Syahrul Borman; Duduik Djaja Sidarta (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Children constitute a vulnerable group requiring protection from sexual crimes, including pedophilia. This research aims to examine criminal law provisions protecting child victims of pedophilia crimes in Indonesia and identify obstacles in their implementation. Using a normative juridical method with statutory and conceptual approaches, the findings demonstrate that legal protection is comprehensively regulated through the Criminal Code (KUHP), the Child Protection Law (Law Number 35 of 2014), Law Number 17 of 2016, and the Electronic Information and Transactions Law (ITE). These regulations provide a strong legal basis both in terms of principal criminal sanctions and additional sanctions such as chemical castration, electronic monitoring device installation, and perpetrator identity disclosure. The regulations also emphasize victims' rights to medical and psychological rehabilitation as well as identity protection. However, implementation faces several obstacles, including low case reporting rates due to stigma and taboo culture, evidentiary difficulties arising from victim trauma, weak inter-agency coordination, limited resources, and the emergence of digital pedophilia modi. Efforts to address these obstacles include strengthening law enforcement capacity, providing child-friendly justice systems, comprehensive rehabilitation services, public legal education, and synergy between government and non-government institutions in child protection.